The Effect of Accounting Information System and Internal Control System on the Quality of Financial Reports at PT Semen Baturaja (Persero) Tbk. - Ciko Arfismanda; Maulan Irwadi; R.M. Rum Hendarmin (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze partially and simultaneously the effect of accounting information systems and internal control systems on the quality of financial reports at PT. Semen Baturaja (Persero) Tbk. The data used came from observation and questionnaires to 60 respondents. This research method uses a quantitative approach using multiple linear regression. The results of the study partially show that both accounting information and internal control system variables have a significant positive effect on the quality of financial statements. The results of the study using the coefficient of determination (R2) obtained a value of 0.464. This shows that the large contribution of the accounting information system and internal control system variables can explain the quality of financial statements by 46.4%, the remaining 53.6% can be explained by other variables not included in this study.